Towards sustainable construction: Harnessing potential of pumice powder for eco-friendly concrete, augmented by hybrid fiber integration to elevate concrete performance - Farooq, Umar; Rizwan, Muhammad; Khaliq, Wasim; Ejaz, Ali; Saingam, Panumas; Hussain, Qudeer; Joyklad, Panuwat (My University, 2024)
This study investigates the innovative use of industrial waste pozzolana, specifically pumice powder (PP), as a partial replacement for cement, combined with hybrid fibers in concrete. Seven formulations varying PP content from 10 % to 35 % were tested, identifying 15 % PP as optimal. PP improved porosity due to its fineness, leading to better homogeneity, a refined microstructure, and an optimum compressive strength of 28.8 MPa with reduced permeability, enhancing durability. Hybrid fibers, including steel fibers (SF) from waste tires and polypropylene fibers (PF), improved toughness, ductility, and resistance to brittle failure. Tests on hybrid fiber-reinforced concrete (HyFRC) mixes with 1 % and 2 % hybrid fibers showed up to an 18.09 % increase in compressive, tensile, and flexural strengths. Energy dissipation in compressive response improved by 544.20 %, while flexural and splitting responses increased by up to 299.65 % and 208.57 %. Durability assessments in hydrochloric (HCl) and sulfuric acid (H2SO4) exposure revealed the synergy of fibers and PP enhanced resistance to chemical degradation, with high PF mixes losing as little as 0.04 % strength. Scanning electron microscopy (SEM) confirmed a dense, well-bonded matrix with reduced porosity. Analytical characterizations of mixtures such as energy dispersive x-ray spectroscopy (EDX) were studied. Regression models developed using Popovic's and Mander's models, accurately predicted HyFRC stress-strain behavior, closely aligning with experimental results. The integration of PP and hybrid fibers not only improved mechanical properties but also extended service life in harsh environments, offering a cost-effective, sustainable concrete solution.
Keywords: Buildings; Cement; Compressive strength; Concrete; Durability; Hybrid fibers; Pumice; Recycling; Regression; Sustainability; Sustainable development